Different affinity of nuclear factor-kappa B proteins to DNA modified by antitumor cisplatin and its clinically ineffective trans isomer - Kasparkova, Jana; Thibault, Thomas; Kostrhunova, Hana; Stepankova, Jana; Vojtiskova, Marie; Muchova, Tereza; Midoux, Patrick; Malinge, Jean-Marc; Brabec, Viktor (The FEBS journal, 2014)
Nuclear factor-kappa B (NF-кB) comprises a family of protein transcription factors that have a regulatory function in numerous cellular processes and are implicated in the cancer cell response to antineoplastic drugs, including cisplatin. We characterized the effects of DNA adducts of cisplatin and ineffective transplatin on the affinity of NF-кB proteins to their consensus DNA sequence (кB site). Although the кB site-NF-κB protein interaction was significantly perturbed by DNA adducts of cisplatin, transplatin adducts were markedly less effective both in cell-free media and in cellulo using a decoy strategy derivatized-approach. Moreover, NF-κB inhibitor JSH-23 [4-methyl-N¹-(3-phenylpropyl)benzene-1,2-diamine] augmented cisplatin cytotoxicity in ovarian cancer cells and the data showed strong synergy with JSH-23 for cisplatin. The distinctive structural features of DNA adducts of the two platinum complexes suggest a unique role for conformational distortions induced in DNA by the adducts of cisplatin with respect to inhibition of the binding of NF-кB to the platinated кB sites. Because thousands of κB sites are present in the DNA, the mechanisms underlying the antitumor efficiency of cisplatin in some tumor cells may involve downstream processes after inhibition of the binding of NF-κB to κB site(s) by DNA adducts of cisplatin, including enhanced programmed cell death in response to drug treatment.
Keywords: Phenylenediamines; NF-кB; sekvence nukleotidů; adukty DNA; Nucleic Acid Conformation; vazebná místa; protinádorové látky; cisplatin; Cell Line, Tumor; Stereoisomerism; HEK293 buňky; Consensus Sequence; modified-oligodeoxynucleotide decoy strategy; Ovarian Neoplasms; DNA nádorová; HEK293 Cells; Drug Synergism; nádory vaječníků; DNA, Neoplasm; synergismus léků; Binding Sites; konformace nukleové kyseliny; stereoizomerie; lidé; ženské pohlaví; antitumor activity; konsenzuální sekvence; Humans; DNA Adducts; NF-kappa B; fenylendiaminy; DNA; cisplatina; Base Sequence; nádorové buněčné linie; Female; Cisplatin; Antineoplastic Agents